Development of Fiqh Learning Module with Inclusive Approach at Madrasah Tsanawiyah - Nur Cholid (Department of Islamic Education, 2021)
The development of learning module is the answer to the teacher’s problems in delivering material to students.. This study aims to determine: 1) how to develop fiqh learning tools with a good inclusion approach to be applied to Madrasah Tsanawiyah; 2) determine the feasibility of the developed learning device product. This research is a research and development (Research and Development). At the design validation stage, the class VII fiqh learning tools with the inclusion approach were validated by two material experts and two media experts. The data collection technique is in the form of a questionnaire instrument. The data from the validation results were then converted to a Likert scale. The results showed that fiqh learning tools with an inclusive approach validated by material and media experts had an excellent quality of material content (with a value of 4.35), the quality of presentation of the material was very good (with a value of 4.52), these results were obtained after testing the second stage. In contrast, the quality of media graphics is very good (with a value of 4.53), and the quality of media language is very good (with a value of 4.33). Moreover, the trial results showed an increase in the average post-test to the pre-test by 17.5 or 29.02%. These results indicate that the fiqh learning tool with the inclusive approach developed is feasible to use as a reference for learning tools.